Hsc70‐induced Changes in Clathrin‐Auxilin Cage Structure Suggest a Role for Clathrin Light Chains in Cage Disassembly. (20th June 2013) - Young, Anna; Stoilova‐McPhie, Svetla; Rothnie, Alice; Vallis, Yvonne; Harvey‐Smith, Phillip; Ranson, Neil; Kent, Helen; Brodsky, Frances M.; Pearse, Barbara M. F.; Roseman, Alan; Smith, Corinne J.
<x xml:space="preserve">Abstract</x> We have used cryo‐electron microscopy to determine the 3D structure of a complex of clathrin, auxilin401‐910 and Hsc70 trapped early in the recruitment of Hsc70 to the clathrin cage. We observed that Hsc70 bound asymmetrically to the clathrin vertex and induced structural changes close to the location of clathrin light chains on the outermost edge of the cage. Clathrin disassembly assays using light scattering suggested that loss of clathrin light chains reduced the efficiency with which auxilin could facilitate disassembly.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>